Influence of electromagnetic (EM) waves polarization modes on surface plasmon resonance - Murat, NF; Mukhtar, WM; Menon, PS; Rashid, ARA; Dasuki, KA; Yussuf, AARA (E D P Sciences, 2024)
Optical sensor based on surface plasmon resonance are widely used for various applications. In this paper, an optimization of EM waves polarization modes for the occurrence of SPR by using a modified optical waveguiding assembly has been discussed. A 633 nm of linearly polarized He-Ne laser was appointed as a light source. The polarization modes were controlled by rotating the position of He-Ne laser. It was found that the optimum SPR signal with reflectance, R = 0.21 a. u and SPR angle, theta(SPR) = 48 degrees can be obtained as the position of laser was rotated at 90 degrees, with the presence of polarizer. The location of the critical angle was observed at theta(C) = 46 degrees. For the validation purpose, a simulation based on Fresnel equation was conducted where the percentage difference between the experimental and theoretical results were analyzed. The percentage difference between experimental and theoretical results for both theta(SPR) and theta(C) were 9.09% and 15.00% respectively. In conclusion, an excellent agreement between the theoretical and experimental findings proved the stability of this SPR setup, where the EM waves polarization can easily be controlled by manipulating the position of laser.